2021
DOI: 10.3345/cep.2019.01543
|View full text |Cite
|
Sign up to set email alerts
|

Changing prevalence of Helicobacter pylori infection in children and adolescents

Abstract: Helicobacter pylori infection has declined over recent decades. However, its prevalence remains high, and nearly 50% of the global population has been infected. In Korea, seroprevalence has steadily decreased in adults, but the status of H. pylori infection in children is unknown. The current status or trend of H. pylori infection in children is important because it can help estimate H. pylori-related diseases including gastric cancer in later life. In this review, the authors discuss the change in H. pylori i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 35 publications
2
26
0
1
Order By: Relevance
“…6 Even with suggestions of a possible link with growth retardation and iron deficiency anaemia in children, limited evidence has affected research efforts. 6,8 In a 2017 study, 9 a global prevalence of 33% was estimated for HPI in childhood, but without a breakdown by sub-regions, countries, and geographical settings which would be quite useful for preventive measures in specific settings. Moreover, no study has systematically reviewed the risk factors for HPI in children.…”
Section: Introductionmentioning
confidence: 99%
“…6 Even with suggestions of a possible link with growth retardation and iron deficiency anaemia in children, limited evidence has affected research efforts. 6,8 In a 2017 study, 9 a global prevalence of 33% was estimated for HPI in childhood, but without a breakdown by sub-regions, countries, and geographical settings which would be quite useful for preventive measures in specific settings. Moreover, no study has systematically reviewed the risk factors for HPI in children.…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori infection in adults is usually chronic and will not heal without specific therapy; on the other hand, spontaneous elimination of the bacterium in childhood is probably relatively common, aided by the administration of antibiotics for other reasons [32]. Based on this assertion, infection among the studied population here could have been due to childhood infection [1,5] and [7] that still persisted within the infected individuals.…”
Section: Discussionmentioning
confidence: 81%
“…In a recent review, Park et al [7] discussed a changing prevalence of Helicobacter pylori infection in children and adolescents. They concluded that age and sex are not significantly associated with H. pylori infection in children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…Although these two values were not big, most individuals were infected by H. pylori at a young age without symptoms. 29,30 And the global prevalence of infection was high, especially in developing countries where it exceeded 50%. 1 Spontaneous H. pylori eradication occurred in infants and children, but the eradication rate decreased with age.…”
Section: Discussionmentioning
confidence: 99%